2010
DOI: 10.1083/jcb.200905059
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of cyclin-dependent kinases are crucial for maintaining genome integrity in S phase

Abstract: WEE1 and CHK1 jointly regulate Cdk activity to prevent DNA damage during replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
155
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(185 citation statements)
references
References 24 publications
25
155
1
Order By: Relevance
“…The gH2AX-positive cells were fairly evenly distributed through S-phase, in contrast to an earlier report by Beck et al in which Wee1 knockdown resulted in the accumulation of gH2AX-labeled cells in late S-phase. 18 Furthermore, unlike the earlier paper, we did not see significant rescue from this effect in any of our 8 Wee1 knockdown clones treated with the general cyclin-dependent kinase (CDK) inhibitor roscovotine (Fig. 1C).…”
Section: Effects Of Wee1 Knockdowncontrasting
confidence: 51%
See 3 more Smart Citations
“…The gH2AX-positive cells were fairly evenly distributed through S-phase, in contrast to an earlier report by Beck et al in which Wee1 knockdown resulted in the accumulation of gH2AX-labeled cells in late S-phase. 18 Furthermore, unlike the earlier paper, we did not see significant rescue from this effect in any of our 8 Wee1 knockdown clones treated with the general cyclin-dependent kinase (CDK) inhibitor roscovotine (Fig. 1C).…”
Section: Effects Of Wee1 Knockdowncontrasting
confidence: 51%
“…Consistently, however, Wee1 knockdown or pharmacological inhibition results in the increased gH2AX labeling of S-phase cells, in vitro and in vivo, as was seen in the present study. This likely reflects increased DNA damage due the unregulated activity of Cdk2, as previously suggested, 18 and provides a rationale for testing Wee1 inhibitors in combination with S-phase specific agents like gemcitabine. However, our results testing the drug combination in 3 orthotopicallygrown PDX models do not provide strong support for this.…”
Section: Mk-1775 (Now Azd1775mentioning
confidence: 90%
See 2 more Smart Citations
“…The mechanism that leads to replication stress in DKO cells is still unknown, and it would be interesting to determine whether it involves illegitimate replication origin firing and fork stalling, as shown for replication stress caused by overexpression of Cdt1 33 or by aberrant CDK activity 34 in some cell types. A controlled CDK activity is key to maintain genome integrity during S phase, 35 and it has been reported that most of the DNA replication stress arises as a result of elevated CDK activity. 36 Interestingly, this phenotype can be alleviated by nucleotide addition.…”
Section: E2f-p53 Regulatory Axis In Tissue Homeostasismentioning
confidence: 99%